(untitled) (Altre Modernità, 2021)
The exile of thousands of Chileans since 1973 generated a set of organizations and collectives in the various host countries. This allowed the creation of countless periodicals that channeled diverse forms of resistance, which were established through cultural and political production. Each journal, inspired by the need to express experiences and reflections generated from Chile and from abroad, poured their expectations in the construction of a universe of possible readers both in Chile, in the group of exiles and in an international community that had to be mobilized. This paper aims to address a set of narratives disseminated in political-cultural periodicals that have a testimonial character. Narratives ranging from denunciatory testimony to more complex forms, as is the case of the painter Guillermo Núñez, who in various records in cultural journals, allows us to recognize that the testimonial function is embedded in the deepest and most dramatic modulation of the human experience that writes to share and leave the trace of suffering individuality and expand in solidarity with others.